2016
DOI: 10.1002/mds.26627
|View full text |Cite
|
Sign up to set email alerts
|

Mutation inADORA1identified as likely cause of early-onset parkinsonism and cognitive dysfunction

Abstract: The known biological activities of A1 R in brain functions including its physical interaction with and inhibitory effect on dopamine receptor D1 provide supportive evidence that disruptions of A1 R may result in neurological dysfunction. Also, recent evidence on the related adenosine A2B receptor marks the domain in which the mutation is positioned as important for function. Finally, ADORA1 is located within the Parkinson's disease locus PARK16, which has been identified in several populations. ADORA1 may be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 57 publications
(113 reference statements)
4
29
2
Order By: Relevance
“…Furthermore, Jaberi and colleagues recently identified a missense PTRHD1 mutation (c.155G>A; p.Cys52Tyr) in a family with early‐onset parkinsonism and cognitive dysfunction . Although they claimed that the strongest candidate gene for the disease was ADORA1 attributed to the role of adenosine receptors in brain function and neuronal activity, there were no substantial proofs to discard PTRHD1 as a causative gene, as was well acknowledged in their report . The PTRHD1 p.Cys52Tyr mutation was predicted to be pathogenic by various computational methods, was found with extremely low frequency in public SNV databases, and was absent in 208 ethnicity‐matched control chromosomes sequenced by us (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Jaberi and colleagues recently identified a missense PTRHD1 mutation (c.155G>A; p.Cys52Tyr) in a family with early‐onset parkinsonism and cognitive dysfunction . Although they claimed that the strongest candidate gene for the disease was ADORA1 attributed to the role of adenosine receptors in brain function and neuronal activity, there were no substantial proofs to discard PTRHD1 as a causative gene, as was well acknowledged in their report . The PTRHD1 p.Cys52Tyr mutation was predicted to be pathogenic by various computational methods, was found with extremely low frequency in public SNV databases, and was absent in 208 ethnicity‐matched control chromosomes sequenced by us (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite PTRHD1 mutations having never been reported in parkinsonism or ID, deletions at the 2p23 locus, encompassing the PTRHD1 gene, are known to be associated with several ID syndromes (Supporting Table 2) . Furthermore, Jaberi and colleagues recently identified a missense PTRHD1 mutation (c.155G>A; p.Cys52Tyr) in a family with early‐onset parkinsonism and cognitive dysfunction . Although they claimed that the strongest candidate gene for the disease was ADORA1 attributed to the role of adenosine receptors in brain function and neuronal activity, there were no substantial proofs to discard PTRHD1 as a causative gene, as was well acknowledged in their report .…”
Section: Discussionmentioning
confidence: 99%
“…Other, more recently identified or rarer mutations await confirmation. There have been instances where initially suggested genes turned out to be—most probably—not pathogenic after subsequent studies, including the diverging observations on EIF4G1 mutations in PD patients and healthy subjects [4, 5], as well as the initial identification of ADORA1 as disease-causing mutations [82] in a family who also have PTRHD1 mutations, and there is ongoing uncertainty on the truly pathogenic variant in the large Canadian Mennonite kindred discussed above, where DNAJC13 and TMEM230 mutations have been postulated to be disease-causing [7••, 28••]. Clinicians need to be aware of possible uncertainties in our present knowledge on these newly discovered genetic entities when providing genetic counseling to patients and families with monogenic forms of PD or Parkinsonism.…”
Section: Resultsmentioning
confidence: 99%
“…Khodadadi et al detected homozygous PTRHD1 c.157C>T (p.H53Y) mutations in two siblings with intellectual disability and motor abnormalities from childhood, who developed muscle stiffness, resting and postural tremor, and anxiety, hypersomnia, and hypersexuality [81••]. Parkinsonism developed as a relatively late part of that syndrome in the late 20s to 30s and was improved by levodopa in daily doses of 300 to 450 mg. Jaberi et al described a second family with two brothers who had a similar clinical presentation [82]. The patients had developed gait disturbance, slowness of movements, tremor, and falls in the mid-20s.…”
Section: New Genes For Recessive and X-linked Pd Or Parkinsonismmentioning
confidence: 99%
“…Parkinson's disease (PD) and dementia with Lewy bodies (DLB) are 2 common neurodegenerative diseases characterized by α‐synuclein inclusions (Lewy bodies) present in the midbrain (PD) or spread throughout the limbic system and neocortex (DLB). A recent study identified a homozygous missense mutation (p.G279S) in the adenosine A1 receptor gene ( ADORA1 ) in an autosomal‐recessive, early‐onset, l ‐dopa‐responsive, consanguineous Iranian family with parkinsonism and cognitive decline . The authors of this study made 2 claims.…”
mentioning
confidence: 99%